To branch or not to branch: C–H selectivity of thiophene-based donor–acceptor–donor monomers in direct arylation polycondensation exemplified by PCDTBT. Issue 32 (25th July 2017) - Lombeck, Florian; Marx, Franziska; Strassel, Karen; Kunz, Susanna; Lienert, Caroline; Komber, Hartmut; Friend, Richard; Sommer, Michael
Abstract : The possibility for unselective C–H activation of a thiophene-based, donor–acceptor–donor monomer during direct arylation polycondensation is investigated. Abstract : Debate remains about potentially occuring non-selective C–H activation during the direct arylation polycondensation of monomers with more than two C–H bonds. Non-selective reactions with dihalides lead to undesirable kinking, branching and cross-linking of conjugated polymer chains, and thus to severe deviations of all opto-electronic properties. Using thiophene–benzothiadiazole–thiophene (TBT) having four different C–H bonds and its popular copolymer with dibromocarbazole, PCDTBT, as an example, we demonstrate that unselective C–H activation, often referred to as "β-arylation", does not occur under typical polycondensation reactions. However, using extreme stoichiometries, i.e. a large excess of halide, model reactions reveal that in addition to the typical α-C–H activation of TBT, γ-arylation takes place. This reaction is also seen in polymer analogous reactions of PCDTBT. If γ-arylation of PCDTBT is mimicked using Suzuki polycondensation with tribrominated TBT, the reaction yield drops significantly, the charge transfer absorption band is blued-shifted and solar cell performance of the corresponding PCBM blends is reduced drastically through both a reduction in short circuit current and fill factor. While many reports have meanwhile shown that direct arylation polymerization can be employed to make well-defined conjugated polymers, this paper demonstrates that (i) unselective arylation of thiophene-based monomers is very unlikely for stoichiometry reasons, (ii) how branching can be identified in donor–acceptor copolymers on a spectroscopic basis and (iii) how the optoelectronic properties change if branching still takes place.